(untitled) (Sebha University Conference Proceedings, 2022)
Corruption is a societal scourge and a global phenomenon that human societies have known since the dawn of history. With a person’s desire to obtain material or moral gains, he used various means, both legal and illegal. Societies are still suffering from the growing problem of the phenomenon of corruption in its various forms. This is happening despite of all the efforts made to combat it. The problem is manifested at the present time that the normal measures and mechanisms are insufficient to combat corruption. It differs from traditional crimes, therefore it is necessary to carefully and objectively study strategies that take into account all aspects of this problem. Accordingly, financial and administrative corruption is represented in the waste of public money. The spread of bribery and preference, the misuse of public money, and the abuse of influence in most government contracts and in the granting of licenses and privileges, all these make such contracts void or voidable, given that they were obtained illegally by “corruption.”